Coleoptera of Dawlish Warren Nature Reserve including a comparison of dry pitfall trapping with shoreline sampling. (30th January 2019) - Armstrong, E; Holloway, G J
Abstract: An examination of community structure and associative niche habitats on the Coleoptera of Dawlish Warren were carried out. The aim of this study was to better understand coleopteran communities frequently ignored in coastal habitats that are at significant risk of becoming endangered due to conflicting coastal human activities and rising sea levels resulting in a coastal squeeze. Here, we hypothesise that the shoreline Coleoptera are an extension of neighbouring coleopteran communities and so will find little difference in community structure. Two techniques were used: pitfall trapping and shoreline sampling. A dry pitfall trap was designed to facilitate live trapping of insects and that guarded against the killing of vertebrates such as sand lizards. Shoreline sampling using a quadrat along a transect was carried out to establish whether this approach could be used as an alternative to pitfall trapping to assess the beetle fauna of the site. Beetles were captured from June until September 2017. A total of 56 species across 15 families were captured with 20 species a first recording for Dawlish Warren. Pitfall traps in the dune system produced 50 species while the shoreline sampling yielded just 13 species. The community structure was observably different between the shoreline and dune system in addition to the disparity in numbers. It was concluded that driftwood and seaweed were important attributes to shoreline coleopteran communities along with a lower pebble presence. Not all of the species in the dunes took to the air to disperse and in doing so exposed themselves to the possibility of becoming stranded in the sea. This point and the fact that a number of beetles captured were shoreline specialists meant that shoreline sampling could not serve as an alternative to pitfall trapping to survey for beetles on this site.